A High-performance Double Side Cooled IGBT Module for EV/HEV Applications - Yaqing MA; Jun YU; Yuekang DU; Jianfeng LI (机车电传动)
High performance, low cost and high reliability integrated power modules for electric vehicle applications are leading the innovation in power electronic technology. In this paper, a high-performance double-sided cooling IGBT power module was developed based on the double-sided cooling packaging structure and the industry advanced packaging technology. From the simulation and test data, the IGBT module has excellent thermal and electrical performance, significantly improved power processing capacity and sufficient power cycle reliability.